Rebranding as an assessment of brand management strategy: The case of Malaysian government linked companies (GLCS) / Rosni Jaafar - Jaafar, Rosni (2013)
This is an exploratory study about organisations using rebranding as a brand management strategy in Malaysia. It aims to identify motivations or reasons for companies to undertake the rebranding exercise and to determine the stages in the rebranding process. Substantial studies on rebranding have been conducted in Europe and the United States where brand management is an acknowledged strategy for successful businesses. This study seeks to document the reasons for rebranding and stages of the rebranding process of Malaysian companies. A comparison of similarities and differences of the Malaysian rebranding experience with existing studies was conducted. Based on the findings a conceptual framework is proposed. This research made use of the qualitative method, using the case study approach and in depth interview for data collection. Two government linked companies Bank Islam Malaysia Berhad and TM Berhad participated in this research. Eisenhardt’s (1989) process of building theories from case studies framework was utilised to develop the research and grounded theory method was adapted in the data analysis. Data sources triangulation serve as a method to enhance the study and in depth interview was the method of primary data collection. Two precipitating drivers for the case studies were finance and corporate strategy change. TM was mainly rebranded to institute a corporate change while Bank Islam rebranded due to financial and corporate circumstances. The Malaysian rebranding process consists of situation analysis (dominated by brand audit), brand identity (development of new brand values, logo and slogan), brand communication and measurement and monitoring. A combination of evolutionary and revolutionary rebranding was implemented for these organisations. Future research can focus on other government linked companies in Malaysia that had undertaken the rebranding exercise